C-Man: Course Management Assistant - Azwan, Abd. Aziz (2006)
Course management systems (CMS) are broadly utilized nowadays and their purpose is to support a teaching and learning environment that includes tools for retrieval of course content, synchronous and asynchronous communication, administrative functions, and assessment. This study identifies the functionalities; of a CMS based on four aspects: course grading, course support material, course notification, and system usability. A prototype called C-Man was built based on the identified functionalities and further tested by potential users to evaluate the prototype usability. The evaluation was based on Computer System Usability Questionnaire (CSUQ) and was performed according to four sub-scales of usability namely the system usefulness, the information or content quality, the interface quality and the overall satisfaction. Overall results showed that majority of the participants satisfied with the C-Man’s usability. Nevertheless, for the future enhancements, recommendations from participants will be taken into considerations.